Increasing returns and market efficiency in agricultural trade - Fafchamps, Marcel; Gabre-Madhin, Eleni Zaude; Minten, Bart (International Food Policy Research Institute, 2003)
Using detailed trader surveys in Benin, Madagascar, and Malawi, this paper investigates the presence of increasing returns in agricultural trade. After analyzing margins, costs, and value added, we find little evidence of returns to scale. Motorized transport is found more cost effective for large loads on longer distances. But transporters pool quantities from multiple traders. Margin rates show little relationship with transaction size. Personal travel costs are a source of increasing returns, but the effect is small. Consequently, total marketing costs are nearly proportional to transaction size. Working and network capital are key determinants of value added. Constant returns to scale in all accumulable factors -- working capital, labor, and network capital -- cannot be projected. This implies that policies to restrict entry into agricultural trade are neither necessary nor useful. Governments should focus instead on technological and institutional innovations to upgrade agricultural markets." -- Authors' Abstract